Nano silver sulfide modified carbon nitride and application thereof, inorganic coating and preparation method thereof
By using nano silver sulfide modified carbon nitride as photocatalyst material and combined with the porous microstructure of inorganic coatings, the problem of insufficient contact of photocatalyst materials in existing coatings is solved, and its catalytic activity and response efficiency are significantly improved, achieving efficient formaldehyde removal and antibacterial and antiviral properties are achieved.
Patent Information
- Application Number
- CN202311226827.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
In existing photocatalyst removal coatings, photocatalyst materials are difficult to contact formaldehyde in the outside air, and their catalytic activity and response efficiency to visible light are insufficient, making it difficult for them to effectively play a role under conventional natural light and fluorescent lamps.
Nano-silver-modified carbon nitride is used as the photocatalyst material, and nano-silver-modified carbon nitride with a three-dimensional porous structure is obtained by calcining nano-silver-sulfide and carbonamide, which enhances its catalytic activity and response efficiency to visible light, and combines it with the porous microstructure in inorganic coatings to ensure full contact between the photocatalyst material and the external environment.
The catalytic activity of photocatalytic materials and the response efficiency to visible light are improved, so that inorganic coatings can remove formaldehyde more effectively, with good antibacterial and antiviral properties, with an efficiency of more than 90% of the aldehyde removal, an efficiency of more than 99.99% of the antibacterial efficiency, and an efficiency of more than 99.9% of the antiviral efficiency.
Smart Images

Figure BDA0004462592920000051 
Figure BDA0004462592920000071 
Figure BDA0004462592920000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of coatings, and more specifically, to a nano silver sulfide modified carbon nitride, an inorganic coating and a preparation method thereof. Background Art
[0002] With the improvement of industrialization level, various chemical products are widely used in all aspects of people's daily life. On the one hand, it has greatly improved people's living standards, and on the other hand, it has also brought some health, environmental protection, safety and health problems. For example, the formaldehyde problem in newly renovated rooms and the increasingly severe harm of bacteria and viruses require our attention. As a vital part of interior decoration, paint, in addition to ensuring its own environmental health, can also bear the burden of purifying indoor air, removing formaldehyde, antibacterial and antiviral. At present, doping photocatalytic materials in coatings is an effective method for preparing formaldehyde-removing and antibacterial materials, that is, effectively decomposing organic free small molecules and killing microorganisms under light conditions.
[0003] However, for existing photocatalyst formaldehyde-removing coatings, on the one hand, the photocatalyst material is wrapped inside the coating and is difficult to contact with formaldehyde in the outside air, making it difficult to play its role in decomposing formaldehyde; on the other hand, photocatalyst materials generally have high requirements for light intensity, and conventional natural light and fluorescent lamps make it difficult for photocatalyst materials to play an effective role. Therefore, it is necessary to improve the catalytic activity of photocatalyst materials and their response efficiency to visible light. Summary of the invention
[0004] In order to allow the photocatalyst material to fully contact with formaldehyde and at the same time improve the catalytic activity of the photocatalyst and the response efficiency to visible light, the present application provides a nano-silver sulfide modified carbon nitride and its application, an inorganic coating and a preparation method thereof.
[0005] In the first aspect, the present application provides a nano silver sulfide modified carbon nitride, using the following technical solution:
[0006] A nano silver sulfide modified carbon nitride is a three-dimensional porous nano silver sulfide modified carbon nitride obtained by calcining nano silver sulfide and carbonamide.
[0007] By adopting the above technical scheme, in the carbon nitride modified by nano-silver sulfide, carbon nitride is mainly used as a graphite phase photocatalyst material; sulfur doping can increase the specific surface area of carbon nitride, thereby exposing more active sites, adjusting the band gap, and reducing the band gap width. Its high crystallinity can accelerate the migration rate of photogenerated electrons in carbon nitride, effectively promote the separation of photogenerated electrons and holes, thereby improving the photocatalytic activity; in addition, silver ions will destroy the cell membrane of microorganisms such as bacteria and viruses when encountering them, playing a role in sterilization and antiviral. At the same time, the three-dimensional porous structure of carbon nitride modified by nano-silver sulfide can make carbon nitride, sulfur and silver ions play their roles better.
[0008] Optionally, the calcination temperature of the nano silver sulfide and carbonamide is 500-600° C. Further, the calcination process of the nano silver sulfide and carbonamide is: calcining the nano silver sulfide and carbonamide at 500-600° C. for 3-5 hours, taking out and grinding, and then calcining at 500-600° C. for 2-3 hours to obtain three-dimensional porous nano silver sulfide modified carbon nitride. Further, the mass ratio of the nano silver sulfide to the carbonamide is 0.1-0.8:1.
[0009] Optionally, the preparation method of nano silver sulfide comprises the following steps: mixing a silver nitrate aqueous solution and a sodium thiosulfate aqueous solution according to a molar mass ratio of silver nitrate to sodium thiosulfate of 1:2-5, letting it stand and taking a supernatant; adding a small amount of hydrochloric acid solution to the supernatant and stirring evenly, letting it stand to obtain a gray precipitate, washing the gray precipitate with deionized water and anhydrous ethanol several times, and then drying it in an oven to obtain nano silver sulfide.
[0010] In a second aspect, the present application provides an application of nano silver sulfide modified carbon nitride, using the following technical solution:
[0011] An application of nano silver sulfide modified carbon nitride, wherein the nano silver sulfide modified carbon nitride is used as a photocatalyst material in inorganic coatings.
[0012] By adopting the above technical scheme, nano silver sulfide modified carbon nitride and inorganic materials are used in combination. On the one hand, the surface of the inorganic material has a porous microstructure, and on the other hand, the nano silver sulfide modified carbon nitride of the present application has a three-dimensional porous structure; the combination of the two allows the nano silver sulfide modified carbon nitride to be very evenly attached to the micropores on the surface of the coating, greatly increasing the contact area between the photocatalyst material and the external environment, and reducing the situation in which the photocatalytic material in traditional latex paint is wrapped in large quantities and cannot contact the external environment and loses its catalytic effect; and the nano silver sulfide modified carbon nitride prepared in the present application has high catalytic activity and response efficiency to visible light in inorganic coatings, and can better remove formaldehyde.
[0013] In a third aspect, the present application provides an inorganic coating, which adopts the following technical solution:
[0014] An inorganic coating comprises the following raw materials by weight: 150-250 parts of silicate solution, 20-80 parts of acrylic emulsion, 4-6 parts of cellulose, 20-50 parts of nano silver sulfide modified carbon nitride, 300-400 parts of filler, 14-42 parts of auxiliary agent and 300-400 parts of water.
[0015] Optionally, the cellulose includes hydroxyethyl cellulose and at least one of hydroxypropyl cellulose, hydroxymethyl cellulose, methyl cellulose and ethyl cellulose, and the hydroxyethyl cellulose includes at least one of nonionic hydroxyethyl cellulose and anionic hydroxyethyl cellulose.
[0016] Optionally, the silicate solution includes at least one of potassium silicate solution, silica sol, and lithium silicate emulsion; the acrylic emulsion includes at least one of styrene acrylic emulsion, pure acrylic emulsion, and silicone acrylic emulsion; and the additives include defoaming agents, wetting dispersants, AMP-95, and silicone hydrophobic agents.
[0017] In a fourth aspect, the present application provides a method for preparing an inorganic coating, using the following technical solution:
[0018] A method for preparing an inorganic coating comprises the following steps:
[0019] Add cellulose and AMP-95 to water, stir until the cellulose is swollen, add a wetting dispersant and a portion of a defoamer, stir evenly, add filler and nano silver sulfide modified carbon nitride, stir and disperse until the fineness is less than 50 μm; then add acrylic emulsion and a portion of the defoamer, stir evenly, then add potassium silicate solution, stir evenly, then add an organosilicon hydrophobic agent and the remaining defoamer, stir and control the viscosity to obtain an inorganic coating.
[0020] In summary, this application has the following beneficial effects:
[0021] 1. In the nano-silver sulfide modified carbon nitride prepared in the present application, sulfur doping improves the catalytic activity of the photocatalyst material, and silver ions give the nano-modified silver sulfide the function of bactericidal and antiviral; in particular, the nano-silver sulfide modified carbon nitride prepared in the preparation method of the present application has a three-dimensional porous structure, which can better enable carbon nitride, sulfur and silver ions to exert their effects.
[0022] 2. After the nano silver sulfide modified carbon nitride of the present application forms a three-dimensional porous structure, it can be well and evenly attached to the surface microporous structure of the inorganic coating, so that the photocatalyst material can fully contact the external environment, reducing the situation where the photocatalyst material is mostly included in the coating; at the same time, the effects of carbon nitride, sulfur and silver ions are more excellent, and can play a good catalytic role, so that the prepared inorganic coating has good formaldehyde removal, antibacterial and antiviral properties, specifically: 24h formaldehyde removal> 90%, 24h antibacterial> 99.99%, 24h antiviral> 99.9%. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments.
[0024] The existing photocatalyst formaldehyde-removing coatings have the following problems: First, the photocatalyst material is wrapped inside the coating and is difficult to contact with formaldehyde in the outside air, making it difficult for it to play its role in decomposing formaldehyde; Second, the photocatalyst material generally has high requirements for light intensity. Conventional natural light and fluorescent lamps make it difficult for the photocatalyst material to play an effective role. The catalytic activity of common photocatalyst materials is not high enough, and their response efficiency to visible light is not fast enough.
[0025] Considering that inorganic coatings are a new type of healthy and environmentally friendly product that meets Class A non-flammability, they do not contain any VOCs themselves. At the same time, their porous surface microstructure is particularly suitable for doping with photocatalyst materials. At the same time, the application of photocatalyst materials in inorganic coatings also reduces the problem of photocatalyst materials losing their photocatalytic effect due to the high-density wrapping effect of the emulsion in latex paints, which makes them unable to contact the external environment.
[0026] However, in the process of doping inorganic coatings and photocatalyst materials, the inventors found that conventional photocatalyst materials were added to inorganic coatings, and the coating did not improve the problem of photocatalyst encapsulation well, and the catalytic activity of conventional photocatalyst materials was not high enough, and the response efficiency to visible light was not fast enough. Therefore, the inventors have developed a three-dimensional porous nano silver sulfide modified carbon nitride after a large amount of research. The above three-dimensional porous nano silver sulfide modified carbon nitride not only has good catalytic activity, but also has a very high response efficiency to visible light, and after the three-dimensional porous nano silver sulfide modified carbon nitride is applied to the inorganic coating system, it can act well with the surface micropores of the inorganic coating, improve the coating to the encapsulation problem of the photocatalyst material, so that the three-dimensional porous nano silver sulfide modified carbon nitride can be fully contacted with formaldehyde, and then the organic coating has good effects such as formaldehyde removal and sterilization.
[0027] The following is an explanation through specific preparation examples, embodiments and application examples.
[0028] Preparation Example of Nano Silver Sulfide
[0029] Preparation Example 1
[0030] Mix the silver nitrate aqueous solution and the sodium thiosulfate aqueous solution in a molar mass ratio of 1:4, let it stand for 2 hours, take the upper clear liquid after standing, then add a small amount of hydrochloric acid solution and stir evenly, let it stand for 24 hours to obtain a gray precipitate, wash the gray precipitate several times with deionized water and anhydrous ethanol, and then dry it in a 60°C oven for 6 hours to obtain nano silver sulfide.
[0031] Example
[0032] This embodiment provides a nano silver sulfide modified carbon nitride, specifically:
[0033] The raw materials include nano silver sulfide and carbonamide in a mass ratio of 0.1-0.8:1.
[0034] The preparation method comprises the following steps:
[0035] After mixing the nano silver sulfide and carbonamide, the mixture is placed in a furnace and calcined at a temperature of 500-600° C., specifically, for 3-5 hours. The material is then taken out and ground to make the material uniformly mixed, and then calcined at a temperature of 500-600° C., specifically, for 2-3 hours, to finally obtain a three-dimensional porous nano silver sulfide modified carbon nitride.
[0036] The following is a detailed description through specific embodiments.
[0037] Example 1
[0038] This embodiment provides a nano silver sulfide modified carbon nitride, and the preparation method thereof comprises the following steps:
[0039] After mixing nano silver sulfide and carbonamide at a mass ratio of 0.5:1, the mixture is placed in a Ma-boiling furnace and calcined at a temperature of 550-580°C for 4 hours. Then the material is taken out and ground to make the material mixed evenly, and then the material is placed in a Ma-boiling furnace and calcined at a temperature of 550-580°C for 3 hours to finally obtain a three-dimensional porous nano silver sulfide modified carbon nitride.
[0040] Example 2-3
[0041] The difference between Example 2-3 and Example 1 is that the process conditions in the preparation process of nano silver sulfide modified carbon nitride are different, as shown in Table 1.
[0042] Table 1 Preparation process conditions of Examples 1-3
[0043]
[0044] Comparative Example
[0045] Comparative Example 1
[0046] The difference between Comparative Example 1 and Example 1 is that the mass ratio of nano silver sulfide to carbonamide is 1.2:1.
[0047] Comparative Example 2
[0048] The difference between Comparative Example 2 and Example 1 is that the calcination temperature of the first calcination is 610-640°C, and the calcination temperature of the second calcination is 610-640°C.
[0049] Comparative Example 3
[0050] The difference between Comparative Example 3 and Example 1 is that the mass ratio of nano silver sulfide to carbonamide is 1.2:1, the calcination temperature of the first calcination is 610-640°C, and the calcination temperature of the second calcination is 610-640°C.
[0051] Application Examples
[0052] The application example of the present application provides an inorganic coating, the raw materials of which include the following components:
[0053] 150-250 parts of silicate solution, 20-80 parts of acrylic emulsion, 4-6 parts of cellulose, 20-50 parts of nano silver sulfide modified carbon nitride, 300-400 parts of filler, 14-42 parts of additives, and 300-400 parts of water.
[0054] Furthermore, the silicate solution includes at least one of potassium silicate solution, silica sol, and lithium silicate solution, and the solid content is 28%-30%; in this specific embodiment, potassium silicate solution is preferred.
[0055] The acrylic emulsion includes at least one of styrene acrylic emulsion, pure acrylic emulsion and silicone acrylic emulsion. In this specific embodiment, styrene acrylic emulsion is preferred.
[0056] Furthermore, the cellulose includes hydroxyethyl cellulose, and also includes at least one of hydroxypropyl cellulose, hydroxymethyl cellulose, methyl cellulose, and ethyl cellulose, wherein the hydroxyethyl cellulose includes at least one of nonionic hydroxyethyl cellulose and anionic hydroxyethyl cellulose. Specifically, the application example of the present application is preferably nonionic hydroxyethyl cellulose.
[0057] Furthermore, the auxiliary agent includes 4-8 parts of defoamer, 4-8 parts of wetting and dispersing agent, 1-2 parts of AMP-95 and 8-20 parts of silicone hydrophobic agent, wherein the defoamer is defoamer SD250, the wetting and dispersing agent is wetting and dispersing agent S60 / 100, and the silicone hydrophobic agent is silicone hydrophobic agent SS1.
[0058] Furthermore, the filler is at least one of titanium dioxide, talc, kaolin, and heavy calcium bentonite. Preferably, the filler in this application example is a mixture of titanium dioxide, kaolin, and heavy calcium bentonite.
[0059] The following is a detailed description using a specific application example.
[0060] Application Example 1
[0061] Application Example 1 provides an inorganic coating, the raw materials of which include the following components:
[0062] 190g silicate solution, 60g acrylic emulsion, 6g cellulose, 20g nano-silver sulfide modified carbon nitride, 335g filler, 20g auxiliary agent, and 360g water.
[0063] The nano silver sulfide modified activated carbon comes from Example 1.
[0064] The filler includes 100g of titanium dioxide, 85g of kaolin and 150g of heavy calcium.
[0065] The additives include 1 g of AMP-95, 5 g of a defoamer, 4 g of a wetting and dispersing agent, and 10 g of a silicone hydrophobic agent.
[0066] This application example also provides a method for preparing an inorganic coating, which specifically comprises the following steps:
[0067] Add hydroxyethyl cellulose and AMP-95 to deionized water, stir for 5 minutes at a speed of 500 r / min, add 2g of defoamer and wetting dispersant after cellulose swells, and disperse for 10 minutes at a speed of 500 r / min; then add titanium dioxide, kaolin, heavy calcium, and nano-silver sulfide modified carbon nitride, adjust the speed to 1500 r / min, and stir and disperse for 30 minutes until the fineness drops below 50 μm; adjust the speed to 600 r / min, add 2g of defoamer and acrylic emulsion in turn, stir and disperse for 10 minutes; then add potassium silicate solution, stir for 10 minutes, and then gradually add silicone hydrophobic agent and 1g of defoamer, stir evenly and control the viscosity at 85±10KU to obtain an inorganic coating.
[0068] Application Example 2-5
[0069] The difference between Application Example 2-5 and Application Example 1 is that the raw materials are different, see Table 2 for details.
[0070] Table 2 Raw materials for application examples 1-5 (unit: g)
[0071]
[0072] Among them, the one addition, two additions and three additions corresponding to the defoaming agent refer to the first addition of the defoaming agent, the second addition of the defoaming agent and the third addition of the defoaming agent in the preparation process respectively.
[0073] Application Example 6
[0074] The difference between Application Example 6 and Application Example 1 is that the nano-silver sulfide-modified carbon nitride comes from Example 2.
[0075] Application Example 7
[0076] The difference between Application Example 7 and Application Example 1 is that the nano-silver sulfide-modified carbon nitride comes from Example 3.
[0077] Comparative Application Examples
[0078] Comparative application example 1
[0079] The difference between Comparative Application Example 1 and Application Example 2 is that: no nano silver sulfide modified carbon nitride is added, and at the same time, the amount of titanium dioxide used is 135g, the amount of heavy calcium used is 200g, and the amount of kaolin used is 50g.
[0080] Comparative Application Example 2
[0081] The difference between Comparative Application Example 2 and Application Example 2 is that 40 g of carbon nitride is used to replace 40 g of nano-silver sulfide modified carbon nitride.
[0082] Comparative Application Example 3
[0083] The difference between Comparative Application Example 3 and Application Example 2 is that 30 g of carbon nitride and 10 g of nano-silver sulfide are used to replace 40 g of nano-silver sulfide-modified carbon nitride.
[0084] Comparative Application Example 4
[0085] The difference between Comparative Application Example 4 and Application Example 2 is that the amount of nano-silver sulfide modified carbon nitride is 60 g.
[0086] Comparative Application Example 5
[0087] The difference between Comparative Application Example 5 and Application Example 2 is that the nano-silver sulfide modified carbon nitride comes from Comparative Example 1.
[0088] Comparative Application Example 6
[0089] The difference between Comparative Application Example 6 and Application Example 2 is that the nano-silver sulfide modified carbon nitride comes from Comparative Example 2.
[0090] Comparative Application Example 7
[0091] The difference between Comparative Application Example 7 and Application Example 2 is that the nano-silver sulfide modified carbon nitride comes from Comparative Example 3.
[0092] Performance testing
[0093] The inorganic coatings obtained in the corresponding use cases and comparative application examples were tested according to the following standards:
[0094] The formaldehyde purification efficiency is tested according to JC / T 1074-2021 standard.
[0095] Antibacterial and antibacterial durability tests are carried out according to HG / T3950-2007 standards.
[0096] Antiviral performance test is carried out according to China Coatings Association T / CNCIA 03002-2022.
[0097] The artificial accelerated aging resistance performance test is carried out according to GB / T1805-2009.
[0098] The specific test results are shown in Table 3
[0099] Table 3 Performance test table of application examples and comparative application examples
[0100]
[0101]
[0102] First, the performance data of the comparative application example and the comparative application example 1 can be found that after the nano silver sulfide modified carbon nitride is added to the inorganic coating system, the formaldehyde removal performance and antiviral performance of the coating are effectively improved, indicating that the nano silver sulfide modified carbon nitride of the present application has good catalytic activity and high light response efficiency. Further analysis of the performance of comparative application example 2 and comparative application example 3 found that comparative application example 2 only uses traditional carbon nitride as a photocatalyst material, and it is found that the formaldehyde removal and antiviral capabilities of the coating are greatly reduced. Comparative application example 3 uses carbon nitride and nano silver sulfide as photocatalyst materials at the same time, and the formaldehyde removal and antiviral performance of the coating are still very poor. This shows that the nano silver sulfide modified carbon nitride of the present application is not a simple composite of carbon nitride and nano silver sulfide, and the effect improvement of the coating of the present application is not from the simple effect superposition between carbon nitride and nano silver sulfide. It is because the nano silver sulfide modified carbon nitride prepared in the present application is a three-dimensional porous structure. Such a special structure allows it to be well and evenly attached to the surface microporous structure of the inorganic coating, so that the photocatalyst material can fully contact the external environment, reducing the situation where the photocatalyst material is mostly included in the coating; at the same time, the three-dimensional porous structure further stimulates the performance of carbon nitride and nano silver sulfide itself. As a result, after the nano silver sulfide modified carbon nitride of the present application is added to the inorganic coating system, it brings good formaldehyde removal and bactericidal and antiviral properties to the coating system.
[0103] At the same time, the performance of application examples 1-3 is analyzed and found that the performance of application example 2 is the most excellent, indicating that too much or too little use of nano silver sulfide modified carbon nitride is not good, especially, it can be more clearly seen from the performance of comparative application example 4 that the use of excessive nano silver sulfide modified carbon nitride is not conducive to the improvement of coating performance. The performance of application examples 4 and 5 is analyzed and found that if the inorganic components in the coating system change, it will also affect the final performance of the coating, which also shows that the nano silver sulfide modified carbon nitride of the present application can work well with the surface microporous structure of the inorganic coating, so that the nano silver sulfide modified carbon nitride can fully contact with formaldehyde.
[0104] As for nano silver sulfide modified carbon nitride, the performance of comparative application examples 5-7 was analyzed and found that in the preparation of the nano silver sulfide modified carbon nitride of comparative application example 5, its raw material ratio was changed, and the coating performance deteriorated; in the preparation of the nano silver sulfide modified carbon nitride of comparative application example 6, its calcination temperature increased, and the coating performance deteriorated. In the preparation of the nano silver sulfide modified carbon nitride of comparative application example 7, while its raw material ratio was changed, the calcination temperature increased, and the coating performance was worse than that of comparative application examples 5-6. This not only shows that the raw material ratio and calcination temperature have an important influence on the synthesis of nano silver sulfide modified carbon nitride. The appropriate ratio and the appropriate calcination temperature enable the nano silver sulfide modified carbon nitride to have a three-dimensional porous structure, which brings good aldehyde removal, bactericidal and antiviral properties to the coating.
[0105] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A nano silver sulfide modified carbon nitride, characterized in that: The nano silver sulfide modified carbon nitride is a three-dimensional porous nano silver sulfide modified carbon nitride obtained by calcining nano silver sulfide and carbonamide.
2. The nano silver sulfide modified carbon nitride according to claim 1, characterized in that: The calcination temperature of the nano silver sulfide and carbonamide is 500-600°C.
3. The nano silver sulfide modified carbon nitride according to claim 2, characterized in that: The calcination process of the nano silver sulfide and carbonamide is as follows: calcining the nano silver sulfide and carbonamide at 500-600° C. for 3-5 hours, taking them out and grinding them, and then calcining them at 500-600° C. for 2-3 hours to obtain three-dimensional porous nano silver sulfide modified carbon nitride.
4. The nano silver sulfide modified carbon nitride according to claim 2, characterized in that: The mass ratio of the nano silver sulfide to carbonamide is 0.1-0.8:
1.
5. The nano silver sulfide modified carbon nitride according to claim 1, characterized in that: The preparation method of nano silver sulfide comprises the following steps: mixing a silver nitrate aqueous solution and a sodium thiosulfate aqueous solution according to a molar mass ratio of silver nitrate to sodium thiosulfate of 1:2-5, and collecting a supernatant after standing; dropping a small amount of hydrochloric acid solution into the supernatant, stirring evenly, and standing to obtain a gray precipitate, washing the gray precipitate with deionized water and anhydrous ethanol for several times, and then drying in an oven to obtain nano silver sulfide.
6. An application of nano silver sulfide modified carbon nitride according to any one of claims 1 to 5, characterized in that: The nano silver sulfide modified carbon nitride is used as a photocatalyst material in inorganic coatings.
7. An inorganic coating according to any one of claims 1 to 5, characterized in that: The raw materials include the following components by weight: 150-250 parts of silicate solution, 20-80 parts of acrylic emulsion, 4-6 parts of cellulose, 20-50 parts of nano silver sulfide modified carbon nitride, 300-400 parts of filler, 14-42 parts of auxiliary agent and 300-400 parts of water.
8. An inorganic coating according to claim 7, characterized in that: The cellulose includes hydroxyethyl cellulose and at least one of hydroxypropyl cellulose, hydroxymethyl cellulose, methyl cellulose and ethyl cellulose. The hydroxyethyl cellulose includes at least one of nonionic hydroxyethyl cellulose and anionic hydroxyethyl cellulose.
9. An inorganic coating according to claim 7, characterized in that: The silicate solution includes at least one of potassium silicate solution, silica sol, and lithium silicate solution; the acrylic emulsion includes at least one of styrene acrylic emulsion, pure acrylic emulsion, and silicone acrylic emulsion; the additives include defoaming agent, wetting dispersant, AMP-95, and silicone hydrophobic agent.
10. A method for preparing an inorganic coating according to any one of claims 7 to 9, characterized in that: The following steps are involved: Add cellulose and AMP-95 to water, stir until the cellulose is swollen, add a wetting dispersant and a portion of a defoamer, stir evenly, add filler and nano silver sulfide modified carbon nitride, stir and disperse until the fineness is less than 50 μm; then add acrylic emulsion and a portion of the defoamer, stir evenly, then add a silicate solution, stir evenly, then add an organosilicon hydrophobic agent and the remaining defoamer, stir to obtain an inorganic coating.
Citation Information
Cited By
A method for preparing a g-C3N4 / chitosan / chlorophyll composite photocatalytic thin film for water purification and its application.
CN122850260A